Early-life undernutrition, immune dysregulation, and cancer incidence in later life: a national life-course analysis from the China health and retirement longitudinal study - Wang, Hailin; Wu, Changkang; Zhou, Xuancheng; Huang, Gang; Li, Jingdong; Tang, Xiaowei (Frontiers in Immunology, 2025)
BackgroundSevere childhood famine may imprint durable immunometabolic scars, yet its longitudinal impact on chronic inflammation and cancer trajectories in China’s ageing population is unresolved.MethodsWe analyzed 2–515 adults in the China Health and Retirement Longitudinal Study (2011–2015) who were born 1947–1961; early-life undernutrition was assigned when birth occurred during 1959–1961 and in one of five provinces with > 30% grain deficit. In parallel, an independent hospital-based verification cohort of 82 adults (recruited 2024–2025) underwent identical exposure classification, biomarker sampling, and cancer surveillance for external validation. High-sensitivity C-reactive protein (hs-CRP), white-blood-cell (WBC) counts, and physician-confirmed malignancies were the prespecified outcomes. Multivariable logistic and Cox mixed-effects models, with interaction terms, quantified dose-response relations and effect modification; estimates from both cohorts were pooled with inverse-variance weighting.ResultsForty-one percent of CHARLS respondents met undernutrition criteria. Compared with unexposed peers, exposed adults showed higher mean hs-CRP (3.18 ± 2.36 vs 2.74 ± 2.11 mg L-¹) and modestly elevated median WBC (6.6 vs 6.3 × 109 L-¹). Undernutrition independently increased the odds of chronic inflammation (hs-CRP ≥ 3 mg L-¹: OR 1.46, 95% CI 1.22–1.75) and leucocytosis (WBC > 10 × 109 L-¹: OR 1.28, 1.04–1.57). Over 9–722 person-years, 122 new cancers occurred; exposed individuals faced a 59% higher hazard (HR 1.59, 1.11–2.27). The verification cohort produced concordant estimates (pooled HR 1.63, 1.23–2.11). Associations were strongest among adults ≥ 60 y or harboring ≥ 2 baseline comorbidities (p-interaction < 0.05).ConclusionDevelopmental caloric deprivation leaves a lasting inflammatory fingerprint that translates into excess mid-life cancer burden. Life-course screening for famine survivors coupled with anti-inflammatory and nutritional interventions will curb malignancy risk as China’s cohort of famine-exposed elders expands.